Buddhists Herminutics: An Analysis of Dhammapada in Sustainable Development (Research Nepal Journal of Development Studies, 2021)
Gautama Buddha, the emblem of peace and love, pioneer of Buddhism, was born in Kapilabastu, Lumbini, Nepal. The peace and love. Compassion in Buddhism is the basic element of Sustainable development. Thus Buddha is the pioneer of sustainable development. Buddha’s text Dhammapada in the present sustainable era is more relevant than past. The paper deals with the hermeneutic analysis of Buddhist’s text Dhammapada in sustainable development. Hermeneutics generally starts from the context of the historical text and ends with the contemporary general understanding. Hermeneutics is concerned with the construction of meaning within the relationship between author/text/reader, and the overarching paradigm. It is the relationship between Buddha, Dhammapada, and sustainable development. It follows six steps as below: 1. Observation and Contextualization; 2. Structural Analysis; 3. Correlation and Interpretation; 4. Fusion of Horizons in Application; 5. Reconstruction, and 6. Generalization of Understanding of the text. The main objective of the study is to find out the contemporary contextual general understanding of Dhammapada in the sustainable development era. The final standpoint of the hermeneutic analysis of Dhammapada on sustainable development is that the peace and prosperity of the people on the planet are only possible through the meaningful partnership in environment protection and right livelihood.